Health guidelines in the Holy Qur’an - Al-Naeem, Abdulaziz Bin Jamal (Edelweiss Applied Science and Technology, 2024)
This research aims to explore the guidelines for psychological and physical health outlined in the Qur’an, as well as the health-related directives regarding drinks and foods mentioned in the Qur’an. The research adopts a descriptive-analytical method and comprises an introduction, a preface, two main sections, and a conclusion. The preface defines the key terms of the study. The first section addresses the guidelines for psychological and physical health in the Qur’an, while the second section examines the Qur’anic instructions concerning beverages and foods and their relationship to healthy nutrition. The conclusion summarizes the key findings, including the notion that health is a fundamental objective of Islam and a significant goal. An individual cannot fulfill their worldly and religious obligations without achieving psychological health and spiritual balance. The research also emphasizes that the Qur’an advocates virtue, prohibits vice, permits wholesome things, and forbids harmful ones. The conclusion presents the main findings along with several recommendations.